AMINO ACID COMPOSITION OF BIFIDOBACTERIAL EXOMETABOLITES AND HYDROLYSATES IN HIV-INFECTED CHILDREN - YULIYA V. Zakharova; LYUDMILA A. Levanova; YULIYA S. Fedorova; ANDREY S. Sukhikh (Фундаментальная и клиническая медицина)
Aim. To study amino acid composition, quantify the amino acids, and investigate neurotropic effects of bifidobacterial exometabolites isolated from HIV-infected children.Materials and Methods. Amino acid composition and quantities in bifidobacterial exometabolites and hydrolysates were measured using reversed-phase high-performance liquid chromatography. An antidepressant activity of exometabolites was evaluated in Balb/c mice by behavioural despair test. Results. The total content of amino acids as well as levels of threonine and serine were 3, 7, and 14-fold higher, respectively, in exometabolites of bifidobacteria isolated from HIV-infected children as compared to those from HIV-negative children. Glycine and histidine were found only in bifidobacterial hydrolysates. Bifidobacteria from HIV-infected children were characterized by high levels of tryptophan and reduced ability to accumulate kynurenine in cells. Exometabolites of bifidobacteria had antidepressant, sedative and stimulating effects on laboratory animals.Conclusions. Bifidobacteria in HIV-infected children are characterized by an increased synthesis of serine, threonine, tryptophan as well as low levels of histidine and glycine production. The ability of bifidobacteria to accumulate the products of the kynurenine pathway of tryptophan oxidation is significantly reduced. The neurotropic effects of bifidobacterial exometabolites are strain-specific.